Salt-corrosion-resistant epoxy resin modified concrete and preparation method thereof

By treating the surface of inorganic materials such as cement and adding nanomaterials such as graphene oxide to the epoxy resin matrix to form a dense barrier layer, the problem of concrete being easily corroded in the marine environment is solved, and corrosion resistance and service life are significantly improved.

CN119504184APending Publication Date: 2025-02-25新疆理工学院
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411582540.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing concrete is susceptible to corrosion in marine environments, resulting in a shortening of the structure's service life. The existing technology has limitations in temperature difference changes, insufficient adhesion and long-term performance decay.

Method used

The surface of inorganic materials such as cement, sand, and gravel is treated with silane coupling agent to enhance interface adhesion, and graphene oxide, nanosilica, zinc powder and zinc phosphate are added to the epoxy resin matrix to form a dense barrier layer to prevent the penetration of moisture and chloride ions.

Benefits of technology

It significantly improves the corrosion resistance, wear resistance and mechanical strength of concrete, extends its service life in marine environments, and reduces the risk of steel bar corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504184A_ABST
    Figure CN119504184A_ABST
Patent Text Reader

Abstract

The invention discloses salt-corrosion-resistant epoxy resin modified concrete and a preparation method thereof.According to the epoxy resin modified concrete, the surface of an inorganic material is treated through a silane coupling agent, the interface bonding force among cement, sand, stone and an epoxy resin matrix is improved, and the adhesion and structural stability of the material are ensured; meanwhile, by introducing an epoxy resin toughening technology, the flexibility and crack resistance of a resin matrix are enhanced, so that the resin matrix can cope with temperature difference change and mechanical impact in a marine environment; besides, through the synergistic effect of graphene oxide and nano silicon dioxide, the compactness and barrier performance of the concrete are further improved, permeation paths of water and chloride ions are reduced, corrosion of steel bars and deterioration of the concrete are effectively prevented, the material is endowed with excellent corrosion resistance, the wear resistance and mechanical strength of the material are remarkably improved, and the service life of the material is prolonged. Therefore, the service life of the concrete in a severe environment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of epoxy resin modified concrete, and in particular relates to salt corrosion resistant epoxy resin modified concrete and a preparation method thereof. Background Art

[0002] In the marine environment, concrete structures are exposed to high humidity, high concentrations of chloride ions, salt spray, seawater and temperature changes for a long time, making them extremely vulnerable to corrosion damage. These harsh conditions will accelerate the corrosion of internal steel bars, causing the concrete to expand, crack and peel, which in severe cases will reduce the bearing capacity of the structure and endanger safety. Chloride ions in seawater are particularly dangerous because they can penetrate the surface of concrete to reach the surrounding steel bars, destroy the passivation layer on the surface of the steel bars, induce electrochemical corrosion processes, and then cause the steel bars to rust, increase internal stress, and cause the structure to fail.

[0003] However, there are a large number of pores and microcracks in the internal structure of ordinary concrete. These microscopic defects form penetration paths for corrosive media. When chloride ions in the marine environment reach the steel bars through these channels, they destroy the passivation layer on the surface of the steel bars, which in turn causes electrochemical corrosion of the steel bars, resulting in rust expansion effect, and cracking and peeling of the concrete. The cumulative effect of this internal corrosion significantly shortens the service life of the concrete structure.

[0004] Although the external coatings and admixtures in the existing technologies have delayed corrosion to a certain extent, these technologies still have limitations in terms of temperature changes, insufficient adhesion and long-term performance degradation. Therefore, in order to improve the long-term durability of concrete in the marine environment, it is urgent to develop new protective materials that are denser, more adhesive and have self-healing ability. In view of this, the present invention is proposed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a salt-corrosion-resistant epoxy resin modified concrete and a preparation method thereof, and solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is: A method for preparing salt-corrosion-resistant epoxy resin modified concrete comprises the following steps: Step (1): Use silane coupling agent to treat the surface of cement, sand, gravel and fly ash. Then, add the surface treated cement, sand, gravel and fly ash to a mixing device in proportion and dry mix for 1-2 minutes. First, use silane coupling agent to treat the surface of cement, sand, gravel and fly ash. The main purpose is to enhance the interfacial adhesion between organic materials and inorganic materials and improve the overall performance of concrete. After mixing evenly, a preliminary dry mix is ​​formed. Silane coupling agent can improve the waterproofness and corrosion resistance of the material by chemically bonding with epoxy resin matrix and inorganic materials. Form a hydrophobic barrier to prevent moisture and corrosive ions from entering the material, thereby enhancing the corrosion resistance. The molecular structure of silane coupling agent has dual functions: one end contains silanol, which can react chemically with the surface of inorganic materials; the other end is an organic group, which can form a chemical bond or physical bond with epoxy resin. Through this interface modification, the silane coupling agent establishes a stable "molecular bridge" between the inorganic material and the epoxy resin, greatly improving the interface bonding strength and reducing the risk of interface cracking and falling off.

[0007] The molecular bridge is established as: When the silane coupling agent encounters the surface of an inorganic material, the siloxane group (Si-OR) will hydrolyze into silanol (Si-OH) and condense with the hydroxyl group (OH) on the inorganic surface to form a Si-O-Si covalent bond. This step allows the coupling agent to firmly adhere to the surface of the inorganic material.

[0008] Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing equipment while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture and water to form a preliminary concrete mixture; Step (3): while wet mixing, taking the epoxy resin matrix, adding 5%-10% of the weight of the epoxy resin matrix to the toughening agent, and mixing them evenly to obtain product ①, then adding graphene oxide and nano-silicon dioxide to the product ①, and mixing them evenly to form product ②; Step (4): mixing the concrete mixture in step (2) with the product ②, and mixing them evenly to obtain a mixture; Step (5): Add zinc powder and zinc phosphate to the mixture, and mix them evenly to obtain a final concrete material with a water-binder ratio of 0.5-0.8.

[0009] Optionally, when preparing product ②, an interfacial stabilizer needs to be added during the mixing process.

[0010] Nanoparticles such as nano-silica and graphene oxide tend to aggregate in epoxy resin or concrete matrix due to their high surface energy, resulting in uneven dispersion of materials. Interface stabilizers can be adsorbed on the surface of nanomaterials, reducing the attraction between particles through electrostatic repulsion or steric hindrance, thereby ensuring that they are evenly dispersed in the mixture to avoid performance degradation. In addition, interface stabilizers can also improve the water resistance and corrosion resistance of composite materials. In synergistic effect with graphene oxide and nano-silica, they can form a dense barrier layer to prevent the penetration of moisture and chloride ions and delay the corrosion of internal steel bars.

[0011] Optionally, the modified concrete includes, by weight, 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 1.6-3.6 parts of fly ash, 11.99 parts of water, 1-5 parts of epoxy resin matrix, 0.05-0.5 parts of toughening agent, 0.001-0.05 parts of graphene oxide, 0.01-0.25 parts of nano-silicon dioxide, 0.0001-0.0075 parts of interface stabilizer, 0.16-0.54 parts of zinc powder, and 0.08-0.18 parts of zinc phosphate, and the water-to-cement ratio of the modified concrete is 0.4-0.65.

[0012] Graphene oxide can improve the compactness of concrete together with nano-silica, and enhance the cathodic protection effect together with zinc powder. Specifically, graphene oxide is a two-dimensional material with an ultra-high specific surface area and a unique layered structure, which can effectively fill the micro-cracks and pores in concrete. Its barrier effect can block the penetration of water and chloride ions, thereby reducing the porosity in concrete. Nano-silica has a very small particle size and can penetrate deep into the micropores of concrete and fill the voids in the microstructure, increasing the compactness of the material. Nano-silica can also undergo secondary hydration reactions with cement hydration products (such as calcium hydroxide) to generate additional calcium silicate hydrates, further enhancing the density of concrete; Zinc is a metal with high electrochemical activity. When the steel bars inside the concrete are corroded by chloride ions, the zinc powder will undergo oxidation reaction first, acting as a sacrificial anode to protect the steel bars from corrosion. This cathodic protection mechanism effectively delays the rusting process of the steel bars. Graphene oxide has good electrical conductivity and can form a continuous conductive network in the concrete, helping the zinc powder to release electrons more efficiently, thereby improving the protection efficiency of the sacrificial anode. Its conductive channel can ensure that the cathodic protection of the zinc powder is evenly covered around the steel bars.

[0013] Furthermore, after nano-silica fills the pores of concrete, it not only reduces the penetration of corrosive media, but also ensures the stability of the conductive path between zinc powder and steel bars, preventing the conductive path from being destroyed by corrosive media.

[0014] Zinc phosphate is a commonly used corrosion inhibitor. It can react with the metal surface to form a dense phosphate protective layer. After this layer of phosphate covers the metal surface, it can prevent oxygen and moisture from contacting the metal and reduce the electrochemical corrosion rate of the metal. Zinc phosphate provides corrosion protection, forming a dense phosphate layer to block the corrosive medium; at the same time, zinc powder acts as a sacrificial anode to provide cathodic protection for the steel bars. This synergistic protection system ensures the long-term durability of the steel bars in a corrosive environment and can significantly slow down the corrosion process even in harsh marine environments.

[0015] The present invention utilizes an interfacial stabilizer to perform surface modification on nano silicon dioxide and graphene oxide to enhance their dispersibility in an epoxy resin matrix. In addition, a silane coupling agent is used to treat the surface of inorganic materials such as cement, sand and gravel, thereby improving the interfacial adhesion between the cement matrix and the epoxy resin matrix, enhancing the bonding force, and reducing the problem of instability of the interface layer. The silane coupling agent is used to modify the surface of fly ash to enhance its interfacial bonding strength with the epoxy resin.

[0016] Optionally, the epoxy resin matrix is ​​one of bisphenol A epoxy resin or flexible epoxy resin, wherein the thermal expansion coefficient of bisphenol A epoxy resin is 30-60x10 -6 / ℃, the thermal expansion coefficient of nano-silicon dioxide is 15-30x10 -6 / ℃, the thermal expansion coefficient of flexible epoxy resin is 50-100 x10 -6 / ℃. The setting of thermal expansion coefficient can reduce the inconsistency of thermal expansion or contraction rates between different materials when exposed to high temperature environment for a long time, which may cause stress inside the coating, and then lead to cracking, peeling or even failure of the coating. Flexible epoxy resin can alleviate the difference in thermal expansion coefficient and reduce the internal stress of the material.

[0017] Optionally, after obtaining the final concrete material, the final concrete material needs to be subjected to a gradual temperature increase and curing treatment, the steps being: Place the mixed material in a curing device, preliminarily heat it to 50°C, and keep it for 2 hours to start the initial cross-linking reaction of the epoxy resin and release the initial internal stress; Next, gradually raise the temperature to 80°C and maintain for 2-4 hours to further accelerate the curing reaction of the epoxy resin and enhance the mechanical strength and interfacial adhesion of the material; Finally, the temperature is raised to 120°C and maintained for 2-3 hours to allow the epoxy resin to fully cure, ensuring the corrosion resistance and ultimate strength of the material. This curing process gradually increases the temperature through low, medium and high temperatures to evenly cross-link the epoxy resin matrix, ensuring that the material's adhesion and corrosion resistance reach optimal levels. The gradual heating process can also release the material's internal stress, reduce the risk of cracking, and improve the durability and service life of the final composite material.

[0018] Optionally, the graphene oxide is in powder form, the particle size of the sand is 0.5-2 mm, and the particle size of the stone is 5-25 mm.

[0019] Optionally, the specific surface area of ​​the nano-silicon dioxide is 220 m 2 / g, apparent density is 55g / L, purity is 99.5%, and average particle size is 30nm.

[0020] Optionally, the toughening agent is one of terminal hydroxyl polybutadiene, polyurethane toughening agent, and terminal hydroxyl toughening agent. Epoxy resin itself is a hard and brittle material. The present invention makes the epoxy resin more flexible when subjected to impact and deformation by adding a toughening agent. This toughening treatment avoids cracking of the coating when subjected to environmental stress or temperature changes, and improves the durability of the material. Optionally, the salt-corrosion-resistant epoxy resin modified concrete prepared by the method for preparing the salt-corrosion-resistant epoxy resin modified concrete.

[0021] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time: The epoxy resin modified concrete of the present invention improves the interface bonding force between cement, sand, gravel and epoxy resin matrix by treating the surface of inorganic materials with silane coupling agent, thereby ensuring the adhesion and structural stability of the material. At the same time, by introducing epoxy resin toughening technology, the flexibility and crack resistance of the resin matrix are enhanced, so that it can cope with temperature changes and mechanical impacts in the marine environment; in addition, the synergistic effect of graphene oxide and nano-silicon dioxide further improves the density and barrier performance of concrete, reduces the penetration path of moisture and chloride ions, effectively prevents steel corrosion and concrete deterioration, not only giving the material excellent corrosion resistance, but also significantly improving its wear resistance and mechanical strength, thereby extending the service life of concrete in harsh environments.

[0022] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 It is a comparison chart of mass loss test results of Examples 1-3 and Comparative Example; Figure 2 It is a comparison chart of the chloride ion permeability test results of Examples 1-3 and Comparative Example; Figure 3 It is a comparison chart of the wear resistance test results of Examples 1-3 and the comparative example; Figure 4 It is a comparison chart of the adhesion strength test results of Examples 1-3 and the comparative example.

[0024] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] In this embodiment, a method for preparing salt-corrosion-resistant epoxy resin modified concrete is provided, comprising the following steps: Step (1): Use silane coupling agent to treat the surface of cement, sand, gravel and fly ash. Then, add the surface treated cement, sand, gravel and fly ash into a mixing device in proportion and dry mix for 1-2 minutes to form a preliminary dry mix after mixing evenly. Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing equipment while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture and water to form a preliminary concrete mixture; Step (3): while wet mixing, taking the epoxy resin matrix, adding 5%-10% of the weight of the epoxy resin matrix to the toughening agent, and mixing them evenly to obtain product ①, then adding graphene oxide and nano-silicon dioxide to the product ①, and mixing them evenly to form product ②; Step (4): mixing the concrete mixture in step (2) with the product ②, and mixing them evenly to obtain a mixture; Step (5): Add 1%-3% zinc powder and 0.5%-1% zinc phosphate to the mixture, and mix well to obtain a final concrete material with a water-binder ratio of 0.5-0.8.

[0031] In the process of preparing product ② of this embodiment, an interfacial stabilizer needs to be added during the mixing process.

[0032] In this embodiment, the modified concrete includes 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 1.6-3.6 parts of fly ash, 11.99 parts of water, 1-5 parts of epoxy resin matrix, 0.05-0.5 parts of toughening agent, 0.001-0.05 parts of graphene oxide, 0.01-0.25 parts of nano-silicon dioxide, 0.0001-0.0075 parts of interface stabilizer, 0.16-0.54 parts of zinc powder, and 0.08-0.18 parts of zinc phosphate, and the water-to-binder ratio of the modified concrete is 0.4-0.65.

[0033] In Examples 1-3, the epoxy resin matrix is ​​one of bisphenol A epoxy resin or flexible epoxy resin, wherein the thermal expansion coefficient of bisphenol A epoxy resin is 30 x 10 -6 / ℃, the thermal expansion coefficient of nano-silicon dioxide is 30x10 -6 / ℃, the thermal expansion coefficient of flexible epoxy resin is 50 x 10 -6 / ℃.

[0034] In Examples 1-3, after obtaining the final concrete material, the final concrete material needs to be subjected to a gradual temperature increase and curing treatment, and the steps are: Place the mixed material in a curing device, preliminarily heat it to 50°C, and keep it for 2 hours to start the initial cross-linking reaction of the epoxy resin and release the initial internal stress; Next, the temperature was gradually raised to 80°C and maintained for 3 hours to further accelerate the curing reaction of the epoxy resin and enhance the mechanical strength and interfacial adhesion of the material. Finally, the temperature is raised to 120°C and maintained for 2 hours to allow the epoxy resin to fully cure, ensuring the corrosion resistance and ultimate strength of the material.

[0035] In Examples 1-3, the graphene oxide is in powder form, the particle size of the sand is 2 mm, and the particle size of the stone is 5 mm.

[0036] In Example 1-3, the specific surface area of ​​nano-silicon dioxide is 220 m 2 / g, apparent density is 55g / L, purity is 99.5%, and average particle size is 30nm.

[0037] In this embodiment, the toughening agent is one of terminal hydroxyl polybutadiene, polyurethane toughening agent and terminal hydroxyl toughening agent.

[0038] In this embodiment, the interfacial stabilizer is Lubrizol Solsperse 24000 dispersant.

[0039] The present invention will now be further described in detail with reference to embodiments.

[0040] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.

[0041] Embodiment 1: A method for preparing salt corrosion resistant epoxy resin modified concrete, comprising the following steps: Step (1): 17 parts of cement, 40.8 parts of sand, 67.08 parts of gravel and 2.5 parts of fly ash are surface treated with a silane coupling agent. The surface treated cement, sand, gravel and fly ash are added to a mixing device in proportion and dry mixed for 2 minutes to form a preliminary dry mixed mixture.

[0042] Step (2): After the dry mixing is completed, gradually add 11.99 parts of water into the mixing equipment, keep stirring, and wet mix for 4 minutes to allow the water to fully combine with the solid components to form a preliminary concrete mixture.

[0043] Step (3): At the same time, 3 parts of bisphenol A epoxy resin matrix are taken, and 0.2 parts of terminal hydroxyl polybutadiene toughening agent are added to the weight of the epoxy resin matrix, and the product ① is obtained after being mixed evenly. Then, 0.01 parts of graphene oxide and 0.1 parts of nano-silicon dioxide are added to the product ①, and 0.0003 parts of Solsperse 24000 dispersant is added during the mixing process, and the product ② is obtained after being mixed evenly.

[0044] Step (4): Mix the preliminary concrete mixture in step (2) with the product ② in step (3), stir evenly, and form a mixture.

[0045] Step (5): Add 0.3 parts of zinc powder and 0.1 parts of zinc phosphate to the mixture and mix well to obtain the final concrete material.

[0046] Embodiment 2: A method for preparing salt-corrosion-resistant epoxy resin modified concrete, comprising the following steps: Step (1): Use a silane coupling agent to perform surface treatment on 16 parts of cement, 40.5 parts of sand, 67.08 parts of gravel, and 1.8 parts of fly ash. Add the surface-treated cement, sand, gravel, and fly ash to a mixing device in proportion and dry mix for 2 minutes to form a preliminary dry-mixed mixture.

[0047] Step (2): After the dry mixing is completed, gradually add 11.99 parts of water into the mixing equipment, keep stirring, and wet mix for 4 minutes to allow the water to fully combine with the solid components to form a preliminary concrete mixture.

[0048] Step (3): At the same time, 4 parts of flexible epoxy resin matrix were taken, and 0.3 parts of polyurethane toughening agent were added to the weight of epoxy resin matrix, and product ① was obtained after being mixed evenly. Then, 0.03 parts of graphene oxide and 0.15 parts of nano-silicon dioxide were added to product ①, and 0.0006 parts of Solsperse 24000 dispersant was added during the mixing process, and product ② was obtained after being mixed evenly.

[0049] Step (4): Mix the preliminary concrete mixture in step (2) with the product ② in step (3) in an amount of 5% to 10% (0.8 to 1.6 parts) of the total weight of the cement mixture, stir evenly, and form a mixture.

[0050] Step (5): Add 0.4 parts of zinc powder and 0.15 parts of zinc phosphate to the mixture and mix well to obtain the final concrete material.

[0051] Embodiment 3: A method for preparing salt corrosion resistant epoxy resin modified concrete, comprising the following steps: Step (1): 18 parts of cement, 41.17 parts of sand, 67.08 parts of gravel and 3.6 parts of fly ash are surface treated with a silane coupling agent. The surface treated cement, sand, gravel and fly ash are added to a mixing device in proportion and dry mixed for 2 minutes to form a preliminary dry mixed mixture.

[0052] Step (2): After the dry mixing is completed, gradually add 11.99 parts of water into the mixing equipment, keep stirring, and wet mix for 4 minutes to allow the water to fully combine with the solid components to form a preliminary concrete mixture.

[0053] Step (3): At the same time, take 5 parts of bisphenol A epoxy resin matrix, add 0.5 parts of terminal hydroxyl toughening agent by weight of epoxy resin matrix, mix well to obtain product ①. Then, add 0.05 parts of graphene oxide and 0.25 parts of nano-silicon dioxide to product ①, and add 0.001 parts of Solspers 24000 dispersant during the mixing process, and mix well to obtain product ②.

[0054] Step (4): Mix the preliminary concrete mixture of step (2) with the product ② in step (3) according to the cement mixture, stir evenly, and form a mixture.

[0055] Step (5): Add 0.54 parts of zinc powder and 0.18 parts of zinc phosphate to the mixture and mix well to obtain the final concrete material.

[0056] Comparative Example 1: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Add 20 parts of cement, 41.17 parts of sand and 67.08 parts of gravel into the mixing equipment in proportion, control the mixing speed at 50 rpm, and dry mix for 2 minutes to ensure that the ingredients are evenly distributed to form a preliminary dry mixture.

[0057] After the dry mixing is completed, 11.99 parts of water are gradually added, the stirring speed is controlled at 60 rpm, and stirring is continued for 5 minutes to finally obtain ordinary concrete material.

[0058] 1.1: Quality loss test The samples were placed in 3.5% NaC l The samples were then taken out every 10 days, the surface was rinsed with deionized water, and the mass changes were recorded after drying. After 60 days of corrosion testing, the mass loss rate (%) of the samples was calculated. 1.2: Chloride ion permeability test The sample was immersed in a saturated sodium chloride solution for 28 days, and the rapid chloride ion penetration test (RCPT) method was used to apply a DC voltage and calculate the chloride ion content passing through the sample. The material's resistance to chloride ion penetration was evaluated based on the amount of chloride ions passing through.

[0059] 1.3: Wear resistance test The wear resistance of concrete samples was tested using a Taber abrasion machine. Then, a load of 1000 g was applied and 6000 abrasion cycles were performed. Subsequently, the mass change of the sample before and after abrasion was recorded and the mass loss was calculated. 1.4: Adhesion strength test A 1mm thick epoxy coating was applied on the concrete surface, and then a pull-out test device was used to test the adhesion strength between the epoxy coating and the concrete substrate. A vertical pull was applied to the cured concrete sample until the coating was peeled off, and the maximum pull-out strength was recorded. The test was repeated 50 times, and the average adhesion strength was calculated. In Examples 1-3, the corrosion resistance of concrete is improved by using graphene oxide and nano-silicon dioxide. Graphene oxide is a two-dimensional nanomaterial with an extremely high specific surface area and excellent protective properties. It can effectively prevent corrosive media such as moisture and salts from entering the interior of concrete by forming a dense barrier. In addition, nano-silicon dioxide, due to its ultra-fine particle size, can fill the microscopic pores in concrete, further reducing the penetration of corrosive media. The epoxy resin matrix is ​​combined with these nanomaterials to provide an additional waterproof and anti-corrosion layer, reducing the mass loss of the material in the marine environment.

[0060] The control group used ordinary concrete, which has more internal pores and lacks a protective layer. Corrosive media such as water and chloride can easily penetrate into the concrete through these pores, causing steel bars to rust and accelerating the deterioration of concrete. Therefore, the mass loss is higher.

[0061] Examples 1-3 significantly improve the material's resistance to chloride ion penetration by adding nano-silicon dioxide and graphene oxide to concrete. Nano-silicon dioxide particles are very small and can effectively fill the tiny pores in concrete, making the material more dense inside, thereby reducing the penetration path of chloride ions. Graphene oxide prevents the penetration of chloride ions through its unique layered structure, forming an effective barrier. At the same time, the epoxy resin matrix provides an additional protective layer, further reducing the chance of chloride ions penetrating through concrete to around the steel bars.

[0062] The control group concrete did not use these modified materials, and there were more pores in the concrete structure, which provided a path for the penetration of chloride ions. When chloride ions penetrated into the steel reinforcement area inside the concrete, they would trigger the corrosion reaction of the steel reinforcement, leading to further deterioration of the concrete structure. Therefore, the chloride ion permeability of the control group was high and could not effectively prevent the penetration of chloride ions.

[0063] In Examples 1-3, nano-silicon dioxide and graphene oxide were used to enhance the hardness and wear resistance of concrete. The uniform dispersion of nano-silicon dioxide in concrete not only fills the microscopic pores, but also significantly improves the wear resistance of concrete through its high hardness. Graphene oxide has excellent mechanical properties and can form an enhanced three-dimensional network structure, providing additional strength support for the material when subjected to stress. In addition, the use of toughening agents makes the material show better toughness and wear resistance when subjected to wear and impact.

[0064] The control group concrete did not use reinforcing materials, and the interface between aggregate and cement paste was relatively fragile, which was more likely to fall off when worn. The surface of the control group concrete was easily damaged under high load and friction, resulting in increased wear on the material surface and greater quality loss.

[0065] Embodiment 1-3 uses the combination of epoxy resin matrix and graphene oxide, nano silicon dioxide, and greatly improves the adhesion strength between epoxy resin and concrete matrix. Epoxy resin is an excellent adhesive that can firmly adhere to the treated concrete surface. Graphene oxide can form a strong physical and chemical bond with the epoxy resin matrix due to its surface functionalization characteristics, making the adhesion stronger. At the same time, nano silicon dioxide has good dispersibility and reinforcement, and can improve the interfacial bonding strength of epoxy resin. The use of toughening agent also further improves the toughness and impact resistance of epoxy resin, and prevents the adhesion strength from decreasing due to stress concentration.

[0066] The concrete in the control group did not use epoxy resin and nanomaterials, and its adhesion strength mainly relied on the mechanical bonding between the cement paste and the surface. Under long-term environmental erosion, the concrete surface gradually deteriorated, resulting in a decrease in adhesion strength. Due to the lack of functional materials to enhance adhesion, the surface is easily affected by moisture, chloride ions and temperature changes, resulting in low adhesion strength.

[0067] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A method for preparing salt-corrosion-resistant epoxy resin modified concrete, characterized in that: The following steps are involved: Step (1): using a silane coupling agent to perform surface treatment on cement, sand, gravel and fly ash, then adding the surface treated cement, sand, gravel and fly ash into a mixing device in proportion and dry mixing for 1-2 minutes to form a preliminary dry mixed mixture after being evenly mixed; Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing equipment while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture and water to form a preliminary concrete mixture; Step (3): while wet mixing, taking the epoxy resin matrix, adding 5%-10% of the weight of the epoxy resin matrix to the toughening agent, and mixing them evenly to obtain product ①, then adding graphene oxide and nano-silicon dioxide to the product ①, and mixing them evenly to form product ②; Step (4): mixing the concrete mixture in step (2) with the product ②, and mixing them evenly to obtain a mixture; Step (5): Add 1%-3% zinc powder and 0.5%-1% zinc phosphate to the mixture, and mix well to obtain a final concrete material with a water-binder ratio of 0.5-0.

8.

2. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: When preparing product ②, an interfacial stabilizer needs to be added during the mixing process.

3. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: The modified concrete includes, by weight, 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 1.6-3.6 parts of fly ash, 11.99 parts of water, 1-5 parts of epoxy resin matrix, 0.05-0.5 parts of toughening agent, 0.001-0.05 parts of graphene oxide, 0.01-0.25 parts of nano-silicon dioxide, 0.0001-0.0075 parts of interface stabilizer, 0.16-0.54 parts of zinc powder, and 0.08-0.18 parts of zinc phosphate, and the water-to-cement ratio of the modified concrete is 0.4-0.

65.

4. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: The epoxy resin matrix is ​​one of bisphenol A epoxy resin or flexible epoxy resin, wherein the thermal expansion coefficient of bisphenol A epoxy resin is 30-60 x 10 -6 / ℃, the thermal expansion coefficient of nano-silicon dioxide is 15-30x10 -6 / ℃, the thermal expansion coefficient of flexible epoxy resin is 50-100 x 10 -6 / ℃.

5. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: After obtaining the final concrete material, the final concrete material needs to be gradually heated and cured, and the steps are as follows: Place the mixed material in a curing device, preliminarily heat it to 50°C-60°C, and keep it for 2-3 hours to start the initial cross-linking reaction of the epoxy resin and release the initial internal stress; Next, gradually raise the temperature to 80°C-100°C and maintain for 2-4 hours to further accelerate the curing reaction of the epoxy resin; Finally, raise the temperature to 120°C-150°C and maintain it for 2-3 hours to allow the epoxy resin to reach a fully cured state.

6. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: The graphene oxide is in powder form, the particle size of the sand is 0.5-2 mm, and the particle size of the stone is 5-25 mm.

7. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: The specific surface area of ​​the nano-silicon dioxide is 220 m 2 / g, apparent density is 55g / L, purity is 99.5%, and average particle size is 30nm.

8. The method for preparing a salt corrosion resistant epoxy resin modified concrete according to claim 1, characterized in that: The toughening agent is one of terminal hydroxyl polybutadiene, polyurethane toughening agent and terminal hydroxyl toughening agent.

9. A salt-corrosion-resistant epoxy resin modified concrete prepared by the method for preparing salt-corrosion-resistant epoxy resin modified concrete according to any one of claims 1 to 8.

Citation Information

Cited By

  • Organic-inorganic hybrid synergistically-modified long-acting corrosion-resistant GFRP (glass fiber reinforced plastic) rib in marine environment and preparation method of long-acting corrosion-resistant GFRP rib

    CN120737395A